Setting Fair Prices – Fundamental Principle Of Sustainable Marketing - Iacob Cătoiu; Diana Maria Vrânceanu; Alina Filip (Amfiteatru Economic Journal, 2010)
In commercial area, the price has a major importance, being frequently considered among the main criteria used in buying decision process. Price fairness derives from equity theory and it is focused on assuring in a transaction a reasonable report between the customer's sacrifice and the value offered by the seller. In three marketing experiments we have evaluated customers' fairness perceptions of differential prices, this tactic being frequently used by sellers. One important finding was that the motive for setting differential prices is important in fairness evaluation. Price differences based on social motives are perceived fairer than those motivated by company's interest. The differential prices on customer category are perceived fairer than zone prices. In all three marketing experiments it was demonstrated that price fairness has a significant influence on value perception and on buying intentions. Fair prices setting is one of the principles sustainable marketing is based on, reflecting a long term orientation for a company. By following this decisional direction, the commercial firm increases the value offered to its customers and it becomes more socially responsible.
Keywords: M14; M31; O10; 330; sustainable development; sustainable marketing; fair price; price fairness; differential prices; distributive fairness; procedural fairness